PYTHON PROGRAMMING LANGUAGE AS A MEANS OF TRAINING FUTURE TEACHERS OF COMPUTER SCIENCE WHEN WORKING WITH ARDUINO - Kyslitsyn, V.; Shevchenko, L.; Umanets, V. (Automatizácia tehnologičeskih i biznes-processov, 2024)
This article explores the possibilities and advantages of using the Python programming language together with Arduino robotics kits in the process of training future computer science teachers in pedagogical educational institutions. Considerable emphasis is placed on analyzing the principles of operation of the simplest programs and devices that can be used to visualize the possibilities of using the Arduino platform and Python libraries to create robots that can be implemented in the educational process and everyday life. The authors have developed the program code and presented a working model of a robot assembled and programmed on the basis of Arduino components to measure humidity in computer laboratories and create automatic plant irrigation systems to maintain proper conditions in classrooms. The article presents an example of integrating the learning of the Python programming language with the use of Arduino robotics kits. This method is aimed at improving the quality of training of future computer science teachers, expanding their methodological arsenal and ensuring the ability to teach students using innovative means. The results of the study and the developed teaching and learning materials will help to interest students in STEM education and prepare a new generation of computer science teachers for the challenges of the modern technological world, expand their methodological arsenal and develop the ability to use integrated technical, engineering and mathematical solutions to solve theoretical and practical problems. In addition, this study can serve as a guide to popularize the use of Arduino and Python in educational institutions, and encourage future computer science teachers to implement STEM and hands-on teaching methods, which will contribute to better student learning and improve the quality of professional education in the field of information technology in general. In general, the study opens up a wide range of opportunities for using modern digital technologies in professional education and stimulates interest in STEM education among computer science teachers and students, thereby contributing to the development of a new generation of engineers and technology leaders. Further research could be aimed at developing specific training courses and methods for integrating the Python programming language and Arduino robotics kits into STEM education. It is important to create interdisciplinary STEM courses with the participation of teachers of computer science, physics, mathematics, vocational education in the IT industry, etc.